Pengaruh Label “Tasya Farasya Approved” Pada Produk Skintific Terhadap Minat Beli yang di Moderasi Brand Awareness - Sadiyah, Halimatus; Anas, M. Yusuf Azwar (Business and Economic Publication, 2025)
This study aims to analyze the influence of the "Tasya Farasya Approved" label on Skintific skincare products on Shopee on consumer purchase intention, moderated by brand awareness. Skintific hopes that Tasya Farasya's content and popularity can build a positive image of the company in the eyes of consumers. Many audiences trust and are influenced by Tasya Farasya's reviews, resulting in increased purchase interest in Skintific products. Even some novice influencers choose Skintific after seeing Tasya's reviews. To date, the official Skintific store on Shopee uses the "Tasya Farasya Approved" label as proof of recognition of the quality of Tasya Farasya's products. The study population was followers of the Shopee account Skintific.ID with a sample of 100 people. Data were collected through questionnaires and analyzed using simple regression and moderated regression. The results showed that the "Tasya Farasya Approved" label had a significant effect, both simultaneously and partially, on consumer purchase intention. Brand awareness was also shown to significantly moderate the relationship